Use of Social Media by the Communication, Informatics, Statistics and Cryptography Service in Disseminating Information to the Community of East Luwu Regency - Fety Dwi Angreny; Syukri Syukri; Nur Wahid (Program Studi Ilmu Komunikasi, FISIP Unismuh Makassar, 2025)
This study aims to determine the effectiveness of using social media in disseminating information and to identify the supporting and inhibiting factors for its success. This research uses qualitative methods with data collection techniques through observation, interviews, and documentation. The results showed that the use of social media by the Communication, Informatics, Statistics and Signals Office of East Luwu Regency had a significant success rate. Social media facilitates the delivery of information without having to go directly to the field, allows rapid and wide distribution of information, and increases satisfaction both internally (Diskominfo staff) and externally (the community). Active users show interest in and comfort with Diskominfo's official accounts, as evidenced by various forms of interaction such as likes, comments and resharing. Supporting factors for success include information disclosure and regulations that support transparency and accountability. Meanwhile, inhibiting factors include limited internal human resources and low public digital literacy, which hinder the optimization of information dissemination evenly.